2016
DOI: 10.1111/jtxs.12188
|View full text |Cite
|
Sign up to set email alerts
|

Textural Complexity Model Foods Assessed with Instrumental and Sensory Measurements

Abstract: The term textural complexity is associated with a range of different perceivable textures and sensations occurring from first bite through to swallow. The aim of this study was to develop gel‐based model foods with “built‐in” levels of textural complexity for use in a wider study of the impact of texture on satiation and satiety. The model foods needed to be quantified for textural complexity and that assessment was conducted using instrumental and sensory measurements model foods of different structural compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 36 publications
(67 reference statements)
7
27
0
Order By: Relevance
“…Finally, some other sensory characterization methods, such as descriptive analysis, have been used to complement TDS. Tang et al () used both techniques to distinguish levels of complexity in model foods. Jourdren et al () correlated the sensory PP scores of a trained panel with instrumental mechanical determinations in the intact food products and stated that the TDS and PP results were coherent and complementary.…”
Section: Relation Of Tds With Other Sensory Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some other sensory characterization methods, such as descriptive analysis, have been used to complement TDS. Tang et al () used both techniques to distinguish levels of complexity in model foods. Jourdren et al () correlated the sensory PP scores of a trained panel with instrumental mechanical determinations in the intact food products and stated that the TDS and PP results were coherent and complementary.…”
Section: Relation Of Tds With Other Sensory Techniquesmentioning
confidence: 99%
“…These attributes accounted for the sensation of the bolus dissolving or disappearing rapidly in the mouth. Indeed, chocolate is taken as reference food to define a Melty sensation ("degree to which the sample melts during mastication") (Tang, Larsen, Ferguson, & James, 2017).…”
Section: Last Stage Of Masticationmentioning
confidence: 99%
“…gelatine gels and chocolate) affect oral breakdown of foods with embedded peanuts. Similarly, other studies showed that bolus properties were directly affected by combining different components varying in mechanical properties in a food (Laguna & Sarkar, 2016;Larsen et al, 2015Larsen et al, , 2016Tang et al, 2017Tang et al, , 2016. The oral breakdown was influenced by the degree of "texture complexity".…”
Section: Rationale and Thesis Outlinementioning
confidence: 77%
“…For liquid, semi-solid and solid foods, rheological properties largely impact bite size, consumption time, and eating rate of consumers, while their effects on chewing rate and chewing cycle duration were found to be limited . When food elements varying in texture are combined within a single bite, oral processing and related perception of a product can be affected (James, 2018;Tang et al, 2017;Tarrega et al, 2016). In this instance, the combination of two gel layers with different mechanical properties resulted in an oral processing behaviour with characteristics in between the chewing patterns of the two layers when consumed separately .…”
Section: Dynamics Of Food Texture Perceptionmentioning
confidence: 99%
See 1 more Smart Citation